2011
DOI: 10.1007/s11258-011-9920-4
|View full text |Cite
|
Sign up to set email alerts
|

Aspen (Populus tremuloides) stands and their contribution to plant diversity in a semiarid coniferous landscape

Abstract: We conducted a field study to determine the relative contributions of aspen (Populus tremuloides), meadow, and conifer communities to local and landscape-level plant species diversity in the Sierra Nevada and southern Cascade Range, northeastern California, USA. We surveyed plant assemblages at 30 sites that included adjacent aspen, conifer, and meadow communities across a 10,000-km 2 region. We statistically investigated patterns in local and landscape-scale plant diversity within and among the three vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 36 publications
0
47
1
Order By: Relevance
“…In the case of relatively pure patches of aspen (Populus tremuloides), cottonwood (Populus trichocarpa & Populus fremontii), and birch (Betula papyrifera & Betula occidentalis), fire exclusion has dramatically reduced their abundance, patch sizes, and vigor (Hessburg et al, 1999a). For their influence on habitat for certain species, landscape biodiversity, and fire behavior (Kuhn et al, 2011;Shinneman et al, 2013), there are clear advantages to revitalizing existing clones and patches, or to restoring their abundance (Jones et al, 2005) near wet meadows and seeps, in areas of seasonally high water table, and in floodplain and riparian areas (Bartos and Campbell, 1998;Campbell and Bartos, 2001;Seager et al, 2013). …”
Section: Box 4 Role Of Hardwoods In Msforestsmentioning
confidence: 99%
“…In the case of relatively pure patches of aspen (Populus tremuloides), cottonwood (Populus trichocarpa & Populus fremontii), and birch (Betula papyrifera & Betula occidentalis), fire exclusion has dramatically reduced their abundance, patch sizes, and vigor (Hessburg et al, 1999a). For their influence on habitat for certain species, landscape biodiversity, and fire behavior (Kuhn et al, 2011;Shinneman et al, 2013), there are clear advantages to revitalizing existing clones and patches, or to restoring their abundance (Jones et al, 2005) near wet meadows and seeps, in areas of seasonally high water table, and in floodplain and riparian areas (Bartos and Campbell, 1998;Campbell and Bartos, 2001;Seager et al, 2013). …”
Section: Box 4 Role Of Hardwoods In Msforestsmentioning
confidence: 99%
“…Montane meadows are key to alpine and subalpine animal communities, hydrological function, and human recreation, agriculture, and economy [11][12][13]. Recent work [4] used high resolution, dynamically downscaled climate models to map refugial meadow networks to identify where climate-sensitive species could persist, and restoration and conservation actions could be focused.…”
Section: Introductionmentioning
confidence: 99%
“…This condition, called Sudden Aspen Decline (SAD), is characterized as a drought and disease cycle, where terrain and edaphic features predispose stands to decline, severe drought initiates decline, and finally, opportunistic insects and pathogens cause extensive damage and frequent mortality Rehfeldt et al, 2009;Worrall et al, 2008). Researchers have suggested that aspen is undergoing a range contraction in the warmest, driest, and most southerly regions of its distribution (Kuhn et al, 2011;Worrall et al, 2013;Zegler et al, 2012). Aspen decline and mortality is largely attributed to drought events and to the gradual warming and drying conditions brought about by global climate change (Worrall et al, 2013).…”
Section: Introductionmentioning
confidence: 99%